Rationality or Intuition? - The Assessment of the Quantum of Damages for Personal injuries in Solomon Islands - Corrin Care, Jennifer (Victoria University of Wellington Law Review, 1997)
The development of a Pacific islands jurisprudence is considered in this article in the specific context of six recent judgments of Solomon Islands' courts, which dealt with the rules relating to the assessment of damages for personal injury. The discussion of the issues and the rules enunciated by courts is of social and economic interest, not only as a matter of Solomon Islands' law but also for its value for other small Pacific states where similar issues are having to be resolved.